MANAJEMEN DAKWAH BERBASIS MULTIMEDIAKULTURAL (STUDI KASUS MASJID AGUNG BAITUL MUKMININ JOMBANG) - HIKMAH, LAILATUL; NURCHOLIS, AHMAD (Universitas Islam Negeri (UIN) Mataram, 2021)
The role of multimedia is very influential for the advancement of preaching, with technology it will be easy to access and attract the attention of mad'u or jama'ah. This study aims to determine the extent to which the implementation of multimediacultural-based da'wah management at Baitul Mukminin Mosque in Jombang. This study uses two types of data, namely primary and secondary. Primary data collection was obtained through interview method with resource persons who played a direct role in the management of the Great Mosque of Baitul Mukminin Jombang, while secondary data was obtained through literature study. The data were analyzed descriptively qualitatively. The result of this research is that the Baitul Mukminin Grand Mosque in Jombang has equipped multimediacultural facilities to support its mosque programs, such as cultural-based recitation which is then uploaded to the mosque's social media to expand the reach of mad'u. The Baitul Mukminin Grand Mosque has also implemented a management function in multimediacultural facilities ranging from planning functions to supervision by mosque administrators. The community also supports multimediacultural-based facilities because all mosque information can be accessed easily and flexibly.